Effects of ambient humidity on the Cochet–Bonnet aesthesiometer. (October 2018) - Lum, Edward; Murphy, Paul
Abstract Purpose The Cochet–Bonnet (COBO) aesthesiometer is the current standard in corneal sensitivity assessment. This study investigates the influence of ambient room humidity levels on the stimulus force exerted by the instrument. Methods A COBO instrument (Luneau Opthalmologie) with 0.12 mm nominal nylon filament diameter was placed in an environment chamber (Electro-tech systems Inc. PA, USA) at 25 °C and relative humidity (%RH) set to either 20–80%, in 10% steps. After 12 h in the chamber at a chosen %RH level, the instrument was removed and exerted force measured by pressing the nylon filament onto the plate of an analytical microbalance (Mettler-Toledo AB265; precision ±0.0001 g) at a perpendicular angle, by a predetermined amount. Exerted force onto the microbalance was recorded in grams for a specified filament length. Procedure was repeated for filament lengths 10–60 mm, in 5 mm steps. The instrument was returned to the chamber and procedure repeated 5 times, before repeating at the next %RH setting (random order). Measurements at each filament lengths were compared using one-way ANOVA and post-hoc Tukey's range test. Ap -value < 0.05 denoted statistical significance. Results Significant differences in exerted force were observed with alteration in %RH levels for each filament length (allp < 0.001). Exerted force decreased significantly with an increase in %RH for all filament lengths, with the average force decreasing by 15% with each 10% rise in %RH. Conclusions This study confirms previous suggestions that the rigidity of the COBO nylon filament is affected by ambient room humidity levels, with implications on the stimulus force delivered by the instrument. A conversion table is provided for converting filament lengths to pressure for a range of relative humidity levels.